MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI TAMAN KANAK-KANAK (TK) KARTINI SELOLEMBU BONDOWOSO - Widodo, Wahyudi (LPPM Universitas Ibnu Sina, 2024)
Abstrak School education is one of the important things for the progress of the nation and State. Advanced schools and students also lie in teachers and principals, so with this the principal as a leader must be able to direct well so that it is far from existing problems. Therefore, good and good management for school principals towards improving teachers is very important. The research used is qualitative or field. The results showed that: 1) Principal Management in improving teacher performance in TK Kartini, namely, covering 4 stages of activities, namely: a) planning b) organizing c) implementation d) supervision. 2) The Management Model applied by the Principal in improving teacher performance is: a) Providing examples to teachers, by fostering good personal relationships, b) Assisting teachers in solving the problems they face, c) Appreciating the strengths and weaknesses of teachers and helping them through counseling, d) Providing provisions in encouraging the strengths, interests, and abilities of teacher members in carrying out duties, e) Emphasize democratic approaches in the formulation of goals and regulations.